Predictive interaction of socio-demographic variables on incidence of pre-eclampsia among pregnant women attending government hospitals in Ibadan, Oyo State Nigeria (2016)
The study examined socio-demographic factors as predictors of preeclampsia among pregnant women attending government hospitals in Ibadan, Oyo State. A descriptive survey research design was adopted for this study. Simple random sampling technique was used to select 460 respondents for the study. Self-developed and validated questionnaires were used to collect data. Inferential statistics of linear regression was used to test hypotheses at 0.05 alpha level. The findings revealed that age, (F(1,458) = 3.105; p<0.05), poverty (F1,458) = 24.386; p<0.05), heredity (F1,458) = 50.154; p<0.05), parity (F1,458) = 123.631; p<0.05) and sedentary lifestyle (F1,458) = 180.903; p<0.05) contributed significantly to preeclampsia. It was concluded that socio-demographic variables predicted incidence of pre-eclampsia. It was suggested that health education programme in which prevention of pre-eclampsiawill be prominent should be organised for pregnant women attending government hospitals in Oyo State, Nigeria.